A FRET-based detection of N-acetylneuraminic acid using CdSe/ZnS quantum dot and exonuclease III-assisted recycling amplification strategy. (15th January 2022) - Chen, Jinri; Sun, Nan; Chen, Haohan; Zhang, Yuting; Wang, Xiaoli; Zhou, Nandi
Graphical abstract: Highlights: Neu5Ac biosensor based on FRET and Exo III-assisted recycling amplification strategy. Not require any modification or purification process for Neu5Ac. The detection limit of Neu5Ac is as low as 24 fM. Excellent performance in real sample detection. Offering great potential for the detection of SAs or SAs modified glycans/lipids. Abstract: N -acetylneuraminic acid (Neu5Ac) is widely spread in many biologically significant glycans of mammals, commonly as a terminal α-glycoside. It is of great significance to develop analytical techniques for detection of Neu5Ac. Herein, a high-sensitive fluorescent biosensor for Neu5Ac has been developed based on FRET between CdSe/ZnS quantum dots (QDs) and BHQ2, as well as exonuclease III (Exo III)-assisted recycling amplification strategy. Employing the specially designed three-level FRET systems and fluorescent signal recovery mechanism, together with five-step recycling signal amplification chain reactions, an ultralow detection limit of 24 fM was achieved. Meanwhile, good linear response ranges within 0.2–12.5 pM and 12.5–1000 pM were founded. The assay has excellent performance in real sample detection, and thus offers great potential for detection of sialic acids modified glycans/lipids in the fields of medical diagnosis and food testing.